LET's CONNECT community mentorship program for youths with peer social problems: Preliminary findings from a randomized effectiveness trial. Issue 7 (6th April 2018) - King, Cheryl A.; Gipson, Polly Y.; Arango, Alejandra; Foster, Cynthia Ewell; Clark, Michael; Ghaziuddin, Neera; Stone, Deborah
Abstract: This study examined the effectiveness of LET's CONNECT (LC), a community mentorship program for youths who report peer social problems, which is based on a positive youth development framework. Participants were 218 youths (66.5% girls), aged 12 to 15 years, who were recruited from an urban medical emergency department and screened positive for bullying victimization, bullying perpetration, and/or low social connectedness. Youths were randomized to LC (n = 106) or the control condition (n = 112). Six‐month outcomes were assessed with self‐report measures of youth social connectedness, community connectedness, thwarted belongingness, depression, self‐esteem, and suicidal ideation. LC was associated with a significant increase in only one of these outcomes, social connectedness (effect size = 0.4). It was associated consistently with trend‐level positive changes for thwarted belongingness (decreased), depression (decreased), community connectedness, and self‐esteem (effect sizes = 0.2). There was no effect on suicidal ideation (effect size = 0.0), and although not a primary outcome, eight youths in the LC condition and seven youths in the control condition engaged in suicidal behavior between baseline and follow‐up. Although LC effect sizes are consistent with those from previous studies of community mentorship, there were multiple challenges to LC implementation that affected dosage and intervention fidelity, and that may account for the lack of stronger positive effects.